2012
DOI: 10.1021/ef301242b
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement on a Skeletal Kinetic Model for Primary Reference Fuel Oxidation by Using a Semidecoupling Methodology

Abstract: A semidecoupling methodology for developing skeletal chemical kinetic models is presented and applied to construct an enhanced skeletal model for PRF (primary reference fuel) oxidation, which consists of 41 species and 124 reactions. The basic idea and the semidecoupling methodology are to consider the oxidation mechanism of alkane as two parts: a comprehensive part to describe detailed reaction processes of C0−C1 radicals and molecules as the 'core' and a skeletal part that couples the 'core' to control the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
143
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 292 publications
(146 citation statements)
references
References 37 publications
3
143
0
Order By: Relevance
“…This makes it possible to integrate the diesel surrogate mechanism into multidimensional CFD models for engine combustion simulations. (6) Several mechanisms for n-heptane, iso-octane, and n-decane have been developed using the decoupling methodology in our previous work [33,34,44]. It has been shown that the predictions from the newly developed mechanisms exhibit reasonable agreement with measurements of ignition delay times, primary species concentrations, laminar flame speeds, and extinction strain rates in fundamental experiments, as well as the auto-ignition, combustion and emission behaviors in compression ignition engines.…”
Section: Decoupling Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…This makes it possible to integrate the diesel surrogate mechanism into multidimensional CFD models for engine combustion simulations. (6) Several mechanisms for n-heptane, iso-octane, and n-decane have been developed using the decoupling methodology in our previous work [33,34,44]. It has been shown that the predictions from the newly developed mechanisms exhibit reasonable agreement with measurements of ignition delay times, primary species concentrations, laminar flame speeds, and extinction strain rates in fundamental experiments, as well as the auto-ignition, combustion and emission behaviors in compression ignition engines.…”
Section: Decoupling Methodologymentioning
confidence: 99%
“…[44]. The major low-temperature reaction pathways for iso-octane oxidation include H-atom abstraction reactions (R14-R16), iso-octyl radical (C 8 H 17 ) oxidation reaction (R17), isomerization reaction (R18), secondary O 2 addition reaction (R19), O 2 C 8 H 16 OOH releasing OH reaction (R20), and ketohydroperoxide (C 8 ket) decomposition reaction (R21).…”
Section: Iso-octane Sub-mechanismmentioning
confidence: 99%
“…Experimental and kinetic studies have been conducted to study the oxidation processes of primary reference fuels (PRF, mixture of n-heptane and iso-octane) and detailed and reduced PRF mechanisms are available from the literature [4,8,[10][11][12][13][14][15][16][17][18][19]. The general oxidation reaction pathways proposed by Curran et al [10,11] have been adopted in many kinetic studies.…”
Section: Introductionmentioning
confidence: 99%
“…Standard k-ε (SKE), in the equilibrium product mixture. In the flamelet model, a chemical kinetic mechanism comprising of 41 species and 124 reactions for n-heptane was used [29].…”
Section: Modelmentioning
confidence: 99%